L’immaginazione sociologica e le conseguenze sociali del Covid-19 - Bonini, Tiziano (Mediascapes Journal, 2020)
This brief contribution aims to apply sociological imagination to the issues that emerged with the Covid-19 crisis and suggests some possible topics and methodologies of research. In the first section I describe three relevant themes, among the many possible ones: 1) the new role of personal data (especially those related to our health); 2) the "mediatisation" of distance; 3) the environmental impact of digital media. In the second section, I conclude with a note on how to set the sociological imagination in motion. Among the possible methods, I suggest the rediscovery/adoption of ethnographic methods, and among them, in particular, auto-ethnography. I maintain that it might be useful to study with an ethnographic approach the sociality produced during these days of confinement, instead of using the usual online questionnaires, which often represent a lazy way, for the researcher, to delegate the work of data production to others. Instead, it would be more interesting to return to participant observation and study media as a practice (Couldry 2004). In the conclusions I briefly sketch how it could still be possible to do ethnography in the field in the age of physical distancing and new possible lockdowns